Pioneer Rocketry Proceedings Report 2021 - Van Oss, Benjamin (Proceedings of the Wisconsin Space Conference, 2023)
<span id="docs-internal-guid-47d377d6-7fff-eddc-53d9-f597f57f35c0" style="font-size: 10pt; font-family: 'Times New Roman'; color: #000000; background-color: transparent; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">The Wisconsin Space Grant Consortium hosts the annual Collegiate Rocket Launch Competition every year. The goal of the competition this year was to design and build a rocket to fly to between 2500 and 3500 ft and record flight data along with additional internal readings. The rocket, “Error :(“, used a CTI I435 motor to lift it to an apogee of 2300 ft.. An onboard electronics bay would take measurements before and during flight and a breakaway USB cable from the launch pad to a ground station allowed communication with the rocket until the point of liftoff.